Implementasi Program Rumah Pintar dalam Meningkatkan Keterampilan Literasi dan Numerasi Dasar Siswa SD - Damayanti, Amelia Eka; Nurrochma, Novenntya Putri Prastiwi; Khansa, Nur Aqila; Persada, Yuris Indria; Wulandari, Septi (Bahasa Indonesia, 2025)
This community service activity aims to address the challenges of low reading, writing, and arithmetic (literacy and numeracy) skills at SDN 1 Surodakan elementary school, especially in rural areas. The community service activity was carried out at SDN 1 Surodakan, Trenggalek Regency, by describing the implementation of the "Smart House" program which aims to improve basic literacy and numeracy skills of students in grades 1-3. The community service program was implemented for 12 weeks involving 27 students in creative and interactive literacy-based learning, facilitated by Elementary School Teacher Education (PGSD) students from Malang State University using descriptive qualitative methods. These activities included reading picture stories, creative writing, dictation, and arithmetic with concrete media, such as counting wheels. The results showed significant improvements in reading (28%), writing (28%), and arithmetic (43%), with an average total increase of 33%, accompanied by increased student activity and self-confidence. However, this program faced obstacles such as difficulty in maintaining student focus and minimal parental support at home. The effectiveness of the approach was measured by comparing students' pre-test and post-test results on the three basic skills. Furthermore, effectiveness was also observed through increased student participation in direct learning. The program's sustainability requires integration of the method into regular learning and synergy between schools, families, and communities as the primary supporters of children's education.   Abstrak Kegiatan pengabdian ini bertujuan untuk mengatasi tantangan rendahnya kemampuan membaca, menulis, dan berhitung (literasi dan numerasi) di sekolah dasar SDN 1 Surodakan, khususnya di wilayah pedesaan. Kegiatan pengabdian dilaksanakan di SDN 1 Surodakan, Kabupaten Trenggalek, dengan mendeskripsikan implementasi program “Rumah Pintar” yang bertujuan meningkatkan keterampilan literasi dan numerasi dasar siswa kelas 1-3. Program pengabdian dilaksanakan selama 12 minggu dengan melibatkan 27 siswa dalam pembelajaran berbasis literasi yang kreatif dan interaktif, difasilitasi oleh mahasiswa PGSD Universitas Negeri Malang menggunakan metode kualitatif deskriptif. Kegiatan ini mencakup membaca cerita bergambar, menulis kreatif, dikte, dan berhitung dengan media konkret, seperti kincir berhitung. Hasil menunjukkan peningkatan signifikan pada membaca (28%), menulis (28%), dan berhitung (43%), dengan rata-rata total peningkatan 33%, disertai peningkatan aktivitas dan kepercayaan diri siswa. Meskipun demikian, program ini menghadapi kendala seperti sulitnya siswa menjaga fokus dan minimnya dukungan orang tua di rumah. Efektivitas pendekatan diukur melalui perbandingan hasil pre-test dan post-test siswa pada tiga aspek keterampilan dasar. Selain itu, efektivitas juga diamati melalui peningkatan partisipasi siswa dalam pembelajaran langsung. Keberlanjutan program membutuhkan integrasi metode ke pembelajaran reguler serta sinergi antara sekolah, keluarga, dan komunitas sebagai pendukung utama pendidikan anak.